Avaliação da satisfação profissional dos servidores em saúde mental - Arantes, Israel da Silva (2016)
This study aims to evaluate the level of job satisfaction of the servers in mental health in the municipality of Rio Verde-GO. This is an analytical cross-sectional study with a quantitative and qualitative approach. It conducted a census, interviewing all 76 servers in mental health who were employed in two CAPS and two psychiatric clinics in the city of Rio Verde. Two questionnaires were used, one occupational sociodemographic and other evaluation of job satisfaction of the team involved with the mental health services (SATIS-BR). A descriptive analysis was made, Kolgomorov-Smirnov normality test, non-parametric tests of Mann-Whitney and Kruskal-Wallis, always with a significance level equal or less than 0.05. The results showed good scores of satisfaction, the overall average being 3.6 (± 0.7). The four analyzed factors of the scale were respectively medium 3.8 (± 0.8), 3.6 (± 0.8), 3.5 (± 0.8) and 3.8 (± 0.9). The highest rates of satisfaction focused on the treatment of patients, the responsibilities as servers, privacy and reliability in the units and in interpersonal relationships. Already the most pronounced dissatisfaction questions were the physical conditions of the units, evaluations of new programs and processes, the working environment, wage policy, the structural conditions of the units and the lack of autonomy in services. It was observed that the greatest professional satisfaction rate of mental health workers was observed, respectively, in the Private Clinic I, Private Clinic II, Public Clinic I and, finally, the Public Clinic II. We conclude that, although the identified scores are good, there are factors that generate dissatisfaction, which shows that the services provided by mental health workers in some aspects should be improved which would make possible a better employee satisfaction and organizational climate most appropriate health professional who works in the mental health area.